Host–Guest Interactions of Cucurbit[7]uril with Nabumetone and Naproxen: Spectroscopic, Calorimetric, and DFT Studies in Aqueous Solution - David Klarić; Valentina Borko; Jelena Parlov Vuković; Viktor Pilepić; Ana Budimir; Nives Galić (Molecules)
The complexation of nabumetone (NAB) and naproxen (NAP) with cucurbit[7]uril (CB7) was investigated in aqueous solution by isothermal titration microcalorimetry, mass spectrometry, NMR spectroscopy, and computation methods. High-resolution mass spectrometry was used for the determination of the binding stoichiometry and the gas-phase stability of the drug–CB7 complex. The doubly charged NH4+ or Na+ adducts of the 1:1 complex were observed in the mass spectra. The dissociation of complexes was monitored at different collision energies, (1–16) eV, leading to the neutral loss of NH3 and the drug, with charge retention observed on CB7. By performing ITC experiments, all the thermodynamic parameters were determined for the NAB-CB7 complex in water at 25 °C. The corresponding values amounted to the following: logK = 4.66 ± 0.01; ΔrG° = −26.7 ± 0.1 kJ/mol; ΔrH° = −20.2 ± 0.7 kJ/mol; TΔrS° = 6.4 ± 0.8 kJ/mol, i.e., the formation of the inclusion complex is enthalpy driven and has a favorable entropy. The inclusion phenomena were further confirmed by NMR spectroscopy (1H, ROESY, and DOSY), suggesting the encapsulation of the naphthalene ring of both drugs inside the CB7 cavity. The results of the DFT calculations and the IGMH analysis were in accordance with the experimental ones, suggesting that van der Waals interactions play a major role in drug–CB7 complexation.